Airplane Parts and Covid Masks: Labour Commuters of North-Western Romania Between Central and Eastern European “Re-industrialisation” and the Global Market - FERENȚ, Andreea (Studia Universitatis Babeș-Bolyai Sociologia, 2024)
This article aims to uncover two main features of ‘re-industrialisation’ in Central and Eastern Europe: the reconfiguration of the economic geography in Northwest Romania and the multiple ways in which the Romanian working class is being integrated into the new economy. Post-socialist shifts towards a low-skilled, flexible, and generally insecure economy have underlined the need for cheap, easily disposable labour, and the emergence of the new economic geography has changed the accumulation of capital in the region and the patterns of labour mobility. Despite massive migration, many have continued to work in the region or have combined migration periods with work close to home. This study explores the different mobilities individuals engage in and seeks to understand why some workers choose to stay and live in the region and how the available opportunities for workers aiming to stay in the region influence their prospects. This study traces the patterns of labour commuting and how this is structured by individuals’ strategies and motivations, as well as the social relationships that support this work. The article analyses labour commuting to two major industrial hubs in the region: one which manufactures aerospace components, and one that produces medical textiles. Both companies are foreign-owned and concentrate a significant proportion of the region’s workforce. The micro-dynamics revealed will contribute to understanding the patterns of work in the specific form of re-industrialisation in contemporary Romania.